Evaluation of the 1-mcp application effect and the controlled atmosphere storage in the postharvest quality of peach in two differents maturity stages - Tonetto de Freitas, S.; Sautter, C.; Silveira, A. C.; Brackmann, A. (Agrociencia Uruguay, 2007)
The present work had the objective to evaluated the 1-methylcyclopropene (1-MCP) effect, applied in the postharvest period, in the quality maintenance of cv. “Eldorado” peach, harvested in different maturity stages. The fruit were stored in cool room without atmosphere modification (RA) and in controlled atmosphere condition with 2 kPa of O2 and 5 kPa of CO2 (CA). After 20 days of storage at 0.5º C plus 4 days of shelf life at 15º C, the 1-MCP showed a not important effect in the quality maintenance. Nevertheless, the 1-MCP had an effect in the firmness maintenance in the fruits that were harvested in a less advanced maturity stage (M1) an stored in CA conditions. No 1-MCP significative effect was showed in the others parameters evaluated. The fruits harvested in a less advanced stage showed highest titratable acidity, a greener epidermis color and a less internal browning independent of the 1-MCP application and the storage´s model (RA, CA).